2022
DOI: 10.3233/jpd-213012
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating Parkinson’s Disease from Essential Tremor Using Transcranial Sonography: A Systematic Review and Meta-Analysis

Abstract: Background: Essential tremor (ET) and the tremor of Parkinson’s disease (PD) are the most common tremors encountered in clinical practice. Especially in early disease stages, discrimination between the tremors of ET and PD can be challenging. Objective: The aim of this study was to evaluate the diagnostic accuracy of transcranial sonography (TCS) of the substantia nigra echogenicity for differential diagnosis of PD versus ET. Methods: A systematic PubMed search identified 512 studies. Sensitivity and specifici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 51 publications
(65 reference statements)
0
9
1
1
Order By: Relevance
“…We focused the search on ICH, tumors, and neurodegenerative diseases to assess the accuracy of TCU in the evaluation of brain parenchyma due to the significant number of studies done in these diseases. Our analysis of neurodegenerative diseases showed an overall lower pooled sensitivity and specificity for the diagnosis of intracranial pathology by TCU in comparison to prior systematic reviews evaluating the utility of TCU for the detection of Parkinson's disease 62–64 . Overall, the accuracy of TCU in neurodegenerative diseases was too low for clinical application in initial triage, due to its much lower image resolution for brain parenchyma compared to computer tomography and magnetic resonance imaging.…”
Section: Discussioncontrasting
confidence: 62%
See 4 more Smart Citations
“…We focused the search on ICH, tumors, and neurodegenerative diseases to assess the accuracy of TCU in the evaluation of brain parenchyma due to the significant number of studies done in these diseases. Our analysis of neurodegenerative diseases showed an overall lower pooled sensitivity and specificity for the diagnosis of intracranial pathology by TCU in comparison to prior systematic reviews evaluating the utility of TCU for the detection of Parkinson's disease 62–64 . Overall, the accuracy of TCU in neurodegenerative diseases was too low for clinical application in initial triage, due to its much lower image resolution for brain parenchyma compared to computer tomography and magnetic resonance imaging.…”
Section: Discussioncontrasting
confidence: 62%
“…Moreover, several neurodegenerative diseases cause functional changes detectable on a positron emission tomography scan before gross structural changes are visible in neuroimaging. A recent review highlighting the detection of substantia nigra echogenicity by TCU suggested possible clinical applications in distinguishing Parkinson's disease from essential tremors with similar sensitivity and specificity but these applications are suitable for diagnosed parkinsonian symptoms requiring further delineation of differential diagnosis 64 . We focused our review on information to help with accuracy of TCU in the initial diagnosis of intracranial pathology.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations